2013
DOI: 10.1177/0306624x12472485
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the HM Prison Service “Thinking Skills Programme” Using Psychometric Assessments

Abstract: The most widely implemented offending behaviour programme in the United Kingdom was Enhanced Thinking Skills (ETS), a cognitive-behavioural group intervention that aimed to develop participant's general cognitive skills. A new offending behaviour programme has been developed to replace ETS: the Thinking Skills Programme (TSP). This study reports an evaluation of the effectiveness of TSP using psychometric assessments. Phasing of the two programmes created an opportunity to compare the two programmes consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…These results are similar to previous research (e.g. Gobbett & Sellen, 2014;McDougall et al, 2009). There was also unexpected significant group differences, the most notable being that of victim hurt denial increasing.…”
Section: Methodssupporting
confidence: 93%
See 4 more Smart Citations
“…These results are similar to previous research (e.g. Gobbett & Sellen, 2014;McDougall et al, 2009). There was also unexpected significant group differences, the most notable being that of victim hurt denial increasing.…”
Section: Methodssupporting
confidence: 93%
“…Its application as a measure of treatment impact has been questioned. Psychometric evaluation is an alternative to this and a standard element of treatment evaluation that captures changes in specific areas targeted by treatment (Gobbett & Sellen, 2014). Positive changes have been reported; McDougall et al (2009) demonstrated treatment effects with a large matched control group using adult male prisoners where impulsivity reduced, offence-focused attitudes decreased, and more personal responsibility was indicated.…”
mentioning
confidence: 99%
See 3 more Smart Citations